Do financial performance and firm’s value affect the quality of corporate social responsibility disclosure: Moderating role of chief executive officer’s power in China - Na, Cao; Tian, Gaoliang; Rauf, Fawad; Naveed, Khwaja (Frontiers in Psychology, 2022)
This paper investigates the correlation between the quality of corporate social responsibility disclosure (CSRD) and financial performance (FP). It also investigates the moderating role of chief executive officer power (CEOP) in the relationship between the quality of CSR disclosure and firm value (FV) in Chinese listed companies. The evidential research used the up-to-date sample (3,248) unbalanced findings for the period of 2014-2020, from the registered Chinese firms in the Shenzhen and Shanghai stock exchanges as samples for the study. As a starting point technique, the STATA 15 has been used to test pooled ordinary least squares (OLS) regression on a sample of Chinese listed. We use one year lagged regression and two SLS regression to monitor the potential endogeneity problem. The imbalance data set was received from the China Stock Market and Accounting Research (CSMAR) web page. Which is the most significant source of information for Chinese publicly listed firms? Data on CSR information items and media reporting are compiled manually. The findings of the study revealed that there are positive financial performance consequences for the companies engaged in the quality of CSR disclosure. We also report that higher CEO power moderate has negatively enhanced the quality of CSR disclosure effect on the financial performance firm value. The research investigates the impact of CSR disclosure and financial performance by presenting evidence of the moderating role of CEO power. Therefore, it is suggested that a higher law for CSR engagement and disclosure be implemented in China, and robust measures for the implementation of CEO power, although there are financial advantages to be gained. A key relevance to the empirical quality of CSR disclosure research can be recognized as the moderating role of CEO power in the quality of CSR disclosure – financial performance and firm value in the Context of Chinese study. The findings are robust with the use of an instrumental variable method.